Beyond Linguistic Proximity: Galicia and Portugal in International Negotiation - Fernández-Souto, Ana Belén (2016)
Studying the actions of several institutions, as well as the popular belief according to which Galician people and Portuguese people have enough common ground as to fully understand each other, this article considers the reality of the matter in the context of international negotiation. We will study the use of the Galician language in international business, and then refute—or not—the hypothesis which indicates that the use of Galician can be the first step in a mutual understanding, but that it is necessary to be more deeply immersed in the language before facing an international negotiation—immersed in a way that also includes cultural knowledge.